The Overview of Health Protocols for Preventing and Controlling of COVID-19 ; A Qualitative Exploration from Rural Area in Indonesia - Riky Ristanto Gari; Rezky Aulia Yusuf; Reza Aril Ahri; Sitti Patimah; Haeruddin (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: The COVID-19 has been spread to all over the world. Numerous people still not obey the health protocols that imposed by government. This study aisms to examine in depth the application of health protocols in preventing and controlling of COVID-19 in Muna District. Methods: This research employed an descriptve qualitative research design using semistructed interviews and a purposive sampling approach. The data collection methods was included indept interviews with some key-persons that responsible for COVID-19 prevention and control programs in Muna Regency of Souteast Sulawesi Province of Indonesia and community members. The informants of this study were the the head of COVID-19 task force as key informant; the head of law deparment, a member of the legislative commission for health, a military member and a police, as well as the public. The data was analysed thematically using Nvivo V.12 Plus Software. Results: 1) The role of militery and police as supervisors in implementing health protocol has been carried out well. 2) The implementation of individual health protocols has been carried out, however people with low level of awareness was still lacking about the importance of implementing health protocols such as washing hands, maintaining distance and wearing masks. 3) The application of health protocols for business actors has been carried out, however business owners may still open their businesses (finances matter) but they are required to apply health protocols. 4) The implementation of health protocols in community groups has been carried out and there are some members of the community who care about handling the acceleration of COVID-19, together with local governments to assist with the implementation of health protocols. 5) The regional government provides guidance to the community to participate in efforts to prevent and control Covid-19, conduct security/surveillance in every day, target mass crowds in some areas. Conclusion: Supervision and implementation among citizen in rural area must be regulated strictly and community empowerment is crucial.